Environmental Issue in a Conflict Zone : The Influence of Security Actors on the Ukrainian-Russian Border - Wija Anarki Andi Cella; Seniwati Seniwati (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The Russian invasion of Ukraine, which began in February 2022, has not only caused a humanitarian crisis but also triggered severe environmental consequences, particularly along the Ukrainian-Russian border. This study explores how military actions, occupation of sensitive ecological zones, and the targeting of industrial and critical infrastructure have led to widespread environmental degradation. Using a qualitative approach grounded in document analysis and legal frameworks, the research highlights how security actors have influenced the scale and nature of environmental damage. The findings reveal serious threats to soil quality, water safety, air purity, and biodiversity, as well as disruptions to waste management and energy systems. The paper also discusses the role of ecocide as a potential legal category for holding actors accountable for deliberate environmental harm. By situating the war within the broader context of environmental security and conflict ecology, the study argues for stronger international mechanisms to address ecological risks in armed conflict and post-war recovery.